1991
DOI: 10.1136/jnnp.54.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Isolated muscle hypertrophy as a sign of radicular or peripheral nerve injury.

Abstract: Two patients with isolated neurogenic hypertrophy of the trapezius muscle due to accessory nerve injury and a patient with neurogenic hypertrophy of the anterior tibial muscle due to chronic radicular lesion L4 are described. Electromyography of the affected muscles showed dense continuing spontaneous discharges of complex potentials. Muscle biopsy performed in two patients showed abundant hypertrophic muscle fibres, identified in one case by ATP-ase reaction as being of predominantly type I. In the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…As in the 2 patients described by Thyagarajan et al [3], we found no musculosceletal injury which could explain the movement disorder thereby excluding a nondystonic spasm [3, 9]. Specifically, no lesion of the accessory nerve could be found in our patients, which might produce painful hypertrophy of the trapezius muscle [10]. The present observation of posttraumatic focal dystonia of the should in 2 additional patients of a different source than the original description [3]lends support to the existence of a true, but probably rare movement disorder.…”
Section: Discussionmentioning
confidence: 48%
“…As in the 2 patients described by Thyagarajan et al [3], we found no musculosceletal injury which could explain the movement disorder thereby excluding a nondystonic spasm [3, 9]. Specifically, no lesion of the accessory nerve could be found in our patients, which might produce painful hypertrophy of the trapezius muscle [10]. The present observation of posttraumatic focal dystonia of the should in 2 additional patients of a different source than the original description [3]lends support to the existence of a true, but probably rare movement disorder.…”
Section: Discussionmentioning
confidence: 48%
“…However, in some situations, CRDs may be massive, associated with local muscle stiffness, hypertrophy and, as in the present case, involuntary postures. This clinical association has been reported for S-1 radiculopathies [7][8][9][10] and infrequently for muscle disease [3,11].…”
supporting
confidence: 63%
“…10,11 In these cases, a peripheral (neurogenic) origin has been indicated by EMG with large and/or complex motor unit potentials and characteristic firing patterns (for example, complex repetitive discharges, myokymia). EMG needle examination of the trapezius muscle was performed on four of our patients; the firing patterns were not characteristic of peripheral pathology and three of the four had normal motor unit potentials.…”
Section: Discussionmentioning
confidence: 99%